52.5k views
2 votes
F(x)=6x-18 sub in f(x/3), f(x)/3

User Tonni
by
5.4k points

1 Answer

3 votes

These are two separate problems: in the first we will have to substitute in a new value for x into the original equation and in the second we will manipulate the preexisting equation for f(x).

To begin, we will sub in f(x/3). To do this, we will substitute each variable x in the equation (in this case there is only one) with x/3, and then simplify the resulting equation.

f(x) = 6x - 18

f(x/3) = 6(x/3) - 18

To simplify, we should distribute the 6 on the right side of the equation.

f(x/3) = 6x/3 - 18

Now, we can divide the first term on the right side to finalize our simplification.

f(x/3) = 2x -18

Secondly, we are asked to find f(x)/3. To do this, we will take our original value for f(x), and then simplify divide that entire function by 3.

f(x) = 6x - 18

f(x)/3 = (6x-18)/3

This means that we must divide each term of the binomial by 3, so we are really computing

f(x)/3 = 6x/3 - 18/3

We can simplify by dividing both of the terms.

f(x)/3 = 2x - 6

Therefore, your answer is that f(x/3) = 2x - 18, but f(x)/3 = 2x - 6. It is important to recognize that these are two similar, yet different, answers.

Hope this helps!


User Fulv
by
5.1k points